background image

Obviously

¬

(

X δ

) and

¬

(

δ

Y

).

For suitable

I

and

J

we have:

(

I

J

)

δ

Y

⇔ ∃

x

atoms

A

(

I

J

)

, y

atoms

B

Y

:

x δ y

⇔ ∃

x

atoms

A

I

atoms

A

J, y

atoms

B

Y

:

x δ y

⇔ ∃

x

atoms

A

I, y

atoms

B

Y

:

x δ y

∨ ∃

x

atoms

A

J, y

atoms

B

Y

:

x δ y

I δ

Y

J δ

Y

;

similarly

X δ

(

I

J

)

X δ

I

X δ

J

for suitable

I

and

J

. Let’s continue

δ

till a funcoid

f

(by the theorem 7):

X

[

f

]

Y ⇔ ∀

X

up

X

, Y

up

Y

:

X δ

Y.

The reverse of (8) implication is trivial, so

X

up

a, Y

up

b

x

atoms

A

X, y

atoms

B

Y

:

x δ y

a δ b.

X

up

a, Y

up

b

x

atoms

A

X, y

atoms

B

Y

:

x δ y

⇔ ∀

X

up

a, Y

up

b

:

X δ

Y

a

[

f

]

b

.

So

a δ b

a

[

f

]

b

, that is [

f

] is a continuation of

δ

.

One of uses of the previous theorem is the proof of the following theorem:

Theorem 17

If

A

,

B

are small sets,

R

P

FCD

(

A

;

B

)

,

x

atoms 1

F

(

A

)

,

y

atoms 1

F

(

B

)

, then

1.

h

T

R

i

x

=

T

{h

f

i

x

|

f

R

}

;

2.

x

[

T

R

]

y

⇔ ∀

f

R

:

x

[

f

]

y

.

Proof

2. Let denote

x δ y

⇔ ∀

f

R

:

x

[

f

]

y

. For every

a

atoms 1

F

(

A

)

,

b

atoms 1

F

(

B

)

X

up

a, Y

up

b

x

atoms

A

X, y

atoms

B

Y

:

x δ y

f

R, X

up

a, Y

up

b

x

atoms

A

X, y

atoms

B

Y

:

x

[

f

]

y

f

R, X

up

a, Y

up

b

:

X

[

f

]

Y

f

R

:

a

[

f

]

b

a δ b.

So, by the theorem 16,

δ

can be continued till [

p

] for some funcoid

p

FCD

(

A

;

B

).

For every funcoid

q

FCD

(

A

;

B

) such that

f

R

:

q

f

we have

x

[

q

]

y

⇒ ∀

f

R

:

x

[

f

]

y

x δ y

x

[

p

]

y

, so

q

p

. Consequently

p

=

T

R

.

From this

x

[

T

R

]

y

⇔ ∀

f

R

:

x

[

f

]

y

.

1. From the former

y

atoms

h

T

R

i

x

y

∩h

T

R

i

x

6

= 0

F

(

B

)

⇔ ∀

f

R

:

y

h

f

i

x

6

= 0

F

(Dst

f

)

y

T

h

atoms

i {h

f

i

x

|

f

R

} ⇔

y

atoms

T

{h

f

i

x

|

f

R

}

for every

y

atoms 1

F

(

A

)

. From this follows

h

T

R

i

x

=

T

{h

f

i

x

|

f

R

}

.

23